2017
DOI: 10.1515/secm-2016-0332
|View full text |Cite
|
Sign up to set email alerts
|

Interface transition layer interaction mechanism for ZTAP/HCCI composites

Abstract: ZrO2-toughened Al2O3 (ZTA, 40%) ceramic particles reinforced by high chromium cast iron (HCCI) matrix composites were fabricated by casting infiltration. The interaction between the ZTA ceramic particles and the matrix by the interface transition layer (ITL) was investigated. From the perspective of interfacial bonding, the ceramic particles and HCCI experienced metallurgical bonding by the ITL. Electron probe microanalysis results demonstrated that Cr, Fe, and Mn diffused from the matrix to the ITL. Transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The new sands were replaced after each test duration to eliminate the 'size effect' of the abrasive sand. The mass changes before and after test were used for evaluating the wear resistance of the samples [9,11,18,[21][22][23][32][33][34]. The mass loss was the average value of three group experimental data to guarantee reproducibility.…”
Section: Three-body Abrasive Wear Test and Characterisationmentioning
confidence: 99%
See 4 more Smart Citations
“…The new sands were replaced after each test duration to eliminate the 'size effect' of the abrasive sand. The mass changes before and after test were used for evaluating the wear resistance of the samples [9,11,18,[21][22][23][32][33][34]. The mass loss was the average value of three group experimental data to guarantee reproducibility.…”
Section: Three-body Abrasive Wear Test and Characterisationmentioning
confidence: 99%
“…On the other hand, the favourable fabrication technique can also improve the wear resistance of composites [33,34]. Qiu et al [33] found that the relative wear resistance of the ZTA reinforced Cr26-based composites prepared by pressure casting was higher than that of the composites prepared by infiltration casting due to their tight interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations